THE ROLE OF COMMUNICATION IN THE FAMILY BY DEVELOPING CHILDREN'S CHARACTER - Firdaus Yuni Dharta; Mohamad Sudi; Moh. Syahri Sauma (Adisam Publisher, 2024)
Family is the first and main place for a child to grow, learn and develop. Children at an early age are free to explore various curiosities that exist in their minds, with help from the environment and parents. At this age, forms of communication play a central role, meaning that the family is highly expected to participate as a model for children to emulate. Children are likened to white paper, the ones who determine whether the paper remains white or not, one of them is their parents. The phenomenon currently experienced by a large number of people in education is that parents surrender their duties completely to the school. In fact, this means that the child's character will not be formed well, because there is no continuity or strengthening of the character instilled by the teacher when the child is outside of school hours. Parents with a cultural background that has been rooted since childhood will teach their children the noble cultural values they got from their father and mother. As noble values are continuously passed down from generation to generation, a child's character can be formed from a pair of fathers and mothers who also have character. Education starts from when fathers and mothers get married and are ready to become parents who will one day have children who will be raised according to the cultural roots of their father and mother. Character can be developed from early childhood. The most effective instillation and development of character is through the process of communication and example from parents to their children.